Analog and Hybrid Computer Programming - Ulmann, Bernd (De Gruyter graduate., 2020)
Analog and hybrid computing recently have gained much interest as analog computers can outperform classical stored-program digital computers in some areas by orders of magnitude. This book gives a thorough introduction to analog and hybrid computer programming by means numerous worked examples from various areas. It is based on a number of introductory and advanced lectures on this topic delivered by the author at several universities.